ORAL ALLERGY SYNDROME (OAS) AKIBAT REAKSI ALERGI MAKANAN - Nanan Nur'aeny (Universitas Baiturrahmah, 2015)
Allergic condition such as itching of the skin, or runny nose and sneezing are widely known, but different case of allergic reaction in the mouth. Are still unknown, one of them is Oral Allergy Syndrome (OAS). Almost everyone knows food allergens such as shrimp, or marine fish, but actually fresh fruits and vegetables also can trigger allergic reactions like OAS in the form of itching or swelling of the lips, tongue, palate, and pharynx. Author intends to provide further information about the OAS in this paper. The mechanism of OAS is a type I, immunoglobulin E-mediated hypersensitivity reaction, common in atopic people with history of atopic rhinitis, bronchial asthma, or urticaria. Food allergen that causes OAS have a cross reaction/ homolog with pollen from protein pathogen respons / PR-10 family, such as Bet v 1 (Birch) and Bet v 2 (Birch). Some OAS allergens from vegetables that homolog with Bet v 1 includes celery (Api g 1) and soybean (Gly m 4), and other allergens from fruits homolog with Bet v 2, such as Ana c1 alergen pineapple. The diagnosis of OAS based on medical history, clinical examination and diagnostic tests includes skin prick test, specific IgE serum, or basophil activation test, and cellular antigen stimulation test with an enzyme-linked immunosorbent assay. Management of OAS consists of non-pharmacological includes information and education to avoid the causes, and give suggestion to eat cooked food. Pharmacologically are prescription of antihistamines or epinephrine injection in case of emergencies. Signs and symptoms of OAS in fact have long been found, but its diagnosis and management are still not widely known. Dentist should know about signs and symptoms of food allergy in the oral mucosa include OAS which caused by fruits and vegetables such as celery, soybean, carrot, apple, pineapple, and strawberry, so finally dentist will provide good management for the patient..